2011
DOI: 10.1093/hmg/ddr269
|View full text |Cite
|
Sign up to set email alerts
|

Association of variants in FRAP1 and PDGFRA with corneal curvature in Asian populations from Singapore

Abstract: Corneal curvature (CC) is a key determinant of major eye diseases, such as keratoconus, myopia and corneal astigmatism. No prior studies have discovered the genes for CC. Here we report the findings from four genome-wide association studies of CC in 10 008 samples from three population groups in Singapore. Our discovery phase surveyed 2867 Chinese and 3072 Malays, allowing us to identify two loci that were associated with CC variation: FRAP1 on chromosome 1p36.2 and PDGFRA on chromosome 4q12. These findings we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 22 publications
8
40
0
Order By: Relevance
“…Besides the cosmopolitan reference panel from 1000G project phase I, we possessed population-specific reference panels for Southeast Asian Malays 16 and South Asian Indians 17 that were generated from highcoverage whole-genome sequencing. The intention is to locate the potential protein-altering variants underpinning the association between 176 genetic loci sieved from the NIH GWAS catalog (http: //www.genome.gov/gwastudies) 18 with either eye-related traits such as corneal curvature (CC), central corneal thickness (CCT), corneal astigmatism (CA) and optic disk area (ODA) [19][20][21][22][23][24][25] or blood lipid measurements such as triglycerides (TGs), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C). [26][27][28][29][30] …”
Section: Introductionmentioning
confidence: 99%
“…Besides the cosmopolitan reference panel from 1000G project phase I, we possessed population-specific reference panels for Southeast Asian Malays 16 and South Asian Indians 17 that were generated from highcoverage whole-genome sequencing. The intention is to locate the potential protein-altering variants underpinning the association between 176 genetic loci sieved from the NIH GWAS catalog (http: //www.genome.gov/gwastudies) 18 with either eye-related traits such as corneal curvature (CC), central corneal thickness (CCT), corneal astigmatism (CA) and optic disk area (ODA) [19][20][21][22][23][24][25] or blood lipid measurements such as triglycerides (TGs), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C). [26][27][28][29][30] …”
Section: Introductionmentioning
confidence: 99%
“…This can be explained on the basis of the compensatory effects of other ocular biometric components, such as corneal curvature that influence the effect of an increased axial length through a flatter cornea 6 . Indeed, in genome-wide association studies (GWASs), some genes found to be associated with corneal curvature were also recently reported to be associated with axial length, but not with refractive error 7,13 .…”
mentioning
confidence: 99%
“…A recent study confirms the implication of PDGFRA in corneal curvature, detecting SNPs of PDGFRA and TRIM29 in Australians of Northern European ancestry [42]. Tripartite motif-containing protein 29 (TRIM29) with multiple zinc finger motifs and a leucine zipper motif, acts as a transcriptional regulatory factor and is involved in carcinogenesis and/or differentiation [42]. However, the same study did not reveal any effect of FRAP1 on corneal curvature [42].…”
Section: Genes Related To Corneal Curvature and Thicknessmentioning
confidence: 88%
“…Tripartite motif-containing protein 29 (TRIM29) with multiple zinc finger motifs and a leucine zipper motif, acts as a transcriptional regulatory factor and is involved in carcinogenesis and/or differentiation [42]. However, the same study did not reveal any effect of FRAP1 on corneal curvature [42].…”
Section: Genes Related To Corneal Curvature and Thicknessmentioning
confidence: 94%
See 1 more Smart Citation